Validating a Pteridophyta Atlas Integrated with Local Wisdom for Enhancing Science Process Skills - Nuraini, Afifah Mei; Susantini, Endang; Kartika Indah, Novita; Ishak, Nor Asniza (Yayasan Nurul Yakin Bunga Tanjung, 2025)
Biology learning in schools is often theoretical and involves less direct exploration, so that students' science process skills have not developed optimally. This study aims to produce and test the validity of Atlas Pteridophyta based on Project-Based Learning (PjBL) and integrated with the local wisdom of the community in the Tahura R. Soerjo area as a biology learning media to train science process skills. The method used in this research is Research and Development (R&D) with the 4D model (Define, Design, Develop, Disseminate). This atlas was developed through field exploration of local fern species that are utilized by the community in the context of culture, medicine, and food, then integrated into project-based activities. Validation was conducted by three validators, namely two lecturers of material and media experts to ensure the accuracy of the concept, and one biology teacher to assess the ease of use of the atlas. The validation used a questionnaire that assessed aspects of presentation, integration with PjBL, and relevance to science process skills. The validation results showed that the atlas had an excellent level of validity, with an average score of 3.95. The aspects of integration with PjBL and science process skills scored 3.92 and 3.85, respectively. Although this atlas has not yet been implemented in schools, its use is planned in the pilot stage in one of the high schools in Jombang for grade 10 students. This research is still limited to expert validation and does not include effectiveness testing in the field, so there is no comparison with other learning methods. Therefore, further research is needed to empirically determine the impact of using the atlas on science process skills. In conclusion, the PjBL-based Atlas of Pteridophyta is feasible for use as a contextual and exploratory biology learning medium. The integration of local wisdom also provides a more authentic learning experience and is relevant to the students' environment.